Sources of variation of DNA methylation in rainbow trout: combined effects of temperature and genetic background. Issue 9 (2nd September 2021) - Lallias, Delphine; Bernard, Maria; Ciobotaru, Céline; Dechamp, Nicolas; Labbé, Laurent; Goardon, Lionel; Le Calvez, Jean-Michel; Bideau, Marjorie; Fricot, Alexandre; Prézelin, Audrey; Charles, Mathieu; Moroldo, Marco; et al.
ABSTRACT: Phenotypic plasticity is a key component of the ability of organisms to respond to changing environmental conditions. In this study, we aimed to study the establishment of DNA methylation marks in response to an environmental stress in rainbow trout and to assess whether these marks depend on the genetic background. The environmental stress chosen here was temperature, a known induction factor of epigenetic marks in fish. To disentangle the role of epigenetic mechanisms such as DNA methylation in generating phenotypic variations, nine rainbow trout isogenic lines with no genetic variability within a line were used. For each line, half of the eggs were incubated at standard temperature (11°C) and the other half at high temperature (16°C), from eyed-stage to hatching. In order to gain a first insight into the establishment of DNA methylation marks in response to an early temperature regime (control 11°C vs. heated 16°C), we have studied the expression of 8 dnmt3 (DNA methyltransferase) genes, potentially involved in de novo methylation, and analysed global DNA methylation in the different rainbow trout isogenic lines using LUMA (LUminometric Methylation Assay). Finally, finer investigation of genome-wide methylation patterns was performed using EpiRADseq, a reduced-representation library approach based on the ddRADseq (Double Digest Restriction Associated DNA) protocol, for six rainbow trout isogenic lines. We have demonstrated that thermal history during embryonic development alters patterns of DNA methylation, but to a greater or lesser extent depending on the genetic background.